Asymmetric effects of exchange rate volatility on trade flows in Nigeria - Mutiu G. Rasaki; Elizabeth O. Oyedepo (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study assesses the symmetric and asymmetric effects of exchange rate volatility on trade flows in Nigeria.Method — The study employs quarterly data and covers the period 1995q1 to 2020q4. The data were sourced from International Financial Statistics (IFS) and Central Bank of Nigeria (CBN) websites. The paper applies both linear ARDL and non-linear ARDL (NARDL) models. These methods are employed to evaluate the symmetric and asymmetric effects of exchange rate volatility.Result — The results from linear ARDL model show that exchange rate volatility has only significant short-run effect on export while it has both short-run and long run effects on the imports. The findings from the non-linear ARDL suggest that exchange rate volatility has neither short run nor long run asymmetric effects on exports. However, the non-linear ARDL model reveals short run and long run asymmetric effects of exchange rate volatility on imports. The findings show that increase in volatility reduces imports while decrease in volatility boosts imports.Contribution — Previous studies have only investigated the symmetric effects of exchange rate volatility on trade balance in Nigeria. This study contributes to the literature by examining the symmetric and asymmetric effects of exchange rate volatility on trade flows, using the GARCH-based measure of exchange rate volatility.